A simple, solvent and catalyst-free green synthetic protocol for α-amino phosphonates - Katla, Ramesh; Sabbavarapu, Narayana Murthy; Konkala, Karnakar; Durga, Nageswar Yadavalli Venkata (European Journal of Chemistry, 2012)
A simple and efficient method for the synthesis of α-amino phosphonates has been developed by using aromatic aldehydes, amines, and trimethyl/triethyl phosphite, under catalyst and solvent free conditions, with the formation of the product in good to excellent yields. This method involves milder reaction conditions, easy work-up, and cleaner reaction profiles, and may have wide spread application in organic synthesis.